Secure Massive MIMO Systems With Limited RF Chains - Zhu, Jun; Xu, Wei; Wang, Ning (IEEE transactions on vehicular technology, 2017)
In future practical deployments of massive multi-input multi-output (MIMO) systems, the number of radio-frequency (RF) chains at the base stations (BSs) may be much smaller than the number of BS antennas to reduce the overall expenditure. In this correspondence, we propose a novel design framework for joint data and artificial noise (AN) precoding in a multiuser massive MIMO system with limited number of RF chains, which improves the wireless security performance. With imperfect channel state information (CSI), we analytically derive an achievable lower bound on the ergodic secrecy rate of any mobile terminal (MT) for both analog and hybrid precoding schemes. The closed-form lower bound is used to determine optimal power splitting between data and AN that maximizes the secrecy rate through simple 1-D search. Analytical and numerical results together reveal that the proposed hybrid precoder, although suffering from reduced secrecy rate compared with the theoretical full-dimensional precoder, is free of the high computational complexity of large-scale matrix inversion and null-space calculations and largely reduces the hardware cost.